Can Imaging Be Used for Inflammatory Arthritis Screening? - Østergaard, Mikkel (Seminars in Musculoskeletal Radiology, 2012)
This article reviews the utility of imaging in the diagnostic work-up of suspected and undifferentiated axial and peripheral inflammatory arthritis. Radiographic findings, that is, late damage but not early inflammation, are part of the classification criteria for rheumatoid arthritis (RA), ankylosing spondylitis, spondyloarthritis (SpA), and psoriatic arthritis (PsA), and they are generally part of the early examination program in arthritis.Computed tomography visualizes calcified tissue with high resolution but is rarely used unless radiography is unclear and MRI unavailable.MRI and ultrasonography (US) allow sensitive visualization and assessment of peripheral inflammatory and destructive joint and soft tissue involvement, and MRI is by far the best available method for detecting inflammation in the spine and sacroiliac joints in early SpA. Thus MRI/US can contribute to an earlier diagnosis of RA, PsA, and SpA.MRI and US are part of the recent American College of Rheumatology/European League against Rheumatism 2010 classification criteria for RA (can be used to count involved joints), and MRI is part of the SpondyloArthritis International Society criteria for axial and peripheral SpA.Thus radiography, MRI, and/or US should be used in clinical practice to contribute to the diagnostic work-up in suspected, but not definite, inflammatory joint disease and early unclassified inflammatory joint disease, and they are also useful in establishing a specific diagnosis of RA. Radiography and particularly MRI are essential in establishing an early diagnosis of axial SpA.
Keywords: undifferentiated arthritis; rheumatoid arthritis; spondyloarthritis; radiography; magnetic resonance imaging; ultrasonography